Sixth Five Year Plan (1978-83) Draft Annual Plan 1979-80. Vol. I Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
Planned development of these islands started in the year 1956 with the introduction of Second Five Year Plan. Priority was given in this Five Year Plan and successive plans to the development of basic infrastructure for the territory. In view of the geographical location of these islands, the territory has many typical problems. the main handicap in the development of these islands is the shipping bottle-neck and means of communication both by road and sea within the islands from one island to and another.
Andaman and Nicobar Administration